RIAP Gyrinops verstegii (Gilg) DOMKE PADA LAHAN DENGAN KEDALAMANMUKA AIR TANAH YANG BERBEDA - Mirna Umagapi; Euis F.S. Pangemanan; Johan A. Rombang; Marthen Th. Lasut (Universitas Sam Ratulangi, 2015)
ABSTRACT This research was done to study the increment of Gyrinops versteegii on lands with different levels of ground water depth, a shallow groundwater depth (45-50 cm) at A location and a deep groundwater depth (90-98 cm) at B location. This study used comparative method and purposive sampling. Variables observed were the increase in trunk diameter and free- branch heigtht of Gyrinops. The number of plant sample used was 6 (six) plants, three (3) plants for each location. The measurement of trunk diameter was done, using a measuring tape, at the base of the stem or at 30 cm from the ground. Free branch height was measured from the base of the stem up to the height of the first branch. These observations were done once a month for a year. The results showed that the growth of plants in two locations had differences in trunk diameter and free-branch height from the first month until the last month of observation. The average increments of trunk diameter and free-branch height in the B location were greater than in the A location. Keywords: increment, the ground water level, Gyrinops versteegii